2016
DOI: 10.1002/glia.23081
|View full text |Cite
|
Sign up to set email alerts
|

Fate of microglia during HIV‐1 infection: From activation to senescence?

Abstract: Microglia support productive human immunodeficiency virus type 1 (HIV-1) infection and disturbed microglial function could contribute to the development of HIV-associated neurocognitive disorders (HAND). Better understanding of how HIV-1 infection and viral protein exposure modulate microglial function during the course of infection could lead to the identification of novel therapeutic targets for both the eradication of HIV-1 reservoir and treatment of neurocognitive deficits. This review first describes micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 208 publications
(219 reference statements)
2
62
0
1
Order By: Relevance
“…In fact, cellular senescence has been identified in microglia (Flanary, Sammons, Nguyen, Walker, & Streit, ), oligodendrocytes (Al‐Mashhadi et al, ), neural stem cells (He et al, ), and even neurons (Jurk et al, ). We have recently demonstrated that microglia can senesce in response to HIV infection and have proposed that microglia may transition from activation to senescence (Chen, Partridge, Sell, Torres, & Martin‐Garcia, ; Chen et al, ). Thus, the link between other CNS cell senescence and age‐associated neurodegenerative disease should be further explored.…”
Section: Conclusion and Unresolved Questionsmentioning
confidence: 99%
“…In fact, cellular senescence has been identified in microglia (Flanary, Sammons, Nguyen, Walker, & Streit, ), oligodendrocytes (Al‐Mashhadi et al, ), neural stem cells (He et al, ), and even neurons (Jurk et al, ). We have recently demonstrated that microglia can senesce in response to HIV infection and have proposed that microglia may transition from activation to senescence (Chen, Partridge, Sell, Torres, & Martin‐Garcia, ; Chen et al, ). Thus, the link between other CNS cell senescence and age‐associated neurodegenerative disease should be further explored.…”
Section: Conclusion and Unresolved Questionsmentioning
confidence: 99%
“…As an example, "humanized" bone marrow chimeric mice are susceptible to brain infection by HIV, when the transplanted cells develop into cells with microglia properties within the CNS (Mathews et al, 2019). In addition, as shown by single cell gene expression analysis, chronic microglia infection in the AIDS brain may result in their functional impairment and senescence, which may impair their homeostatic function in chronic brain inflammation (Chen, Partridge, Sell, Torres, & Martin-Garcia, 2017;Ginsberg et al, 2018).…”
Section: Activated Microglia and Macrophages Are Abundant In Active Msmentioning
confidence: 99%
“…Although cART suppresses viral replication, some viral proteins such as Tat, are still made by infected macrophages, microglia, and astrocytes. Viral proteins released from infected glia can harm adjacent neurons directly or indirectly by activating the immune system and triggering the production of cytokines, complement proteins, and reactive oxygen species (Bansal et al, ; Buscemi, Ramonet, & Geiger, ; Chen, Partridge, Sell, Torres, & Martin‐Garcia, ; Jadhav, Krause, & Singh, ; Marker et al, ; Nitkiewicz et al, ; Williams et al, ; Youn, Ju, Choi, & Park, ). Simply exposing the brain to Tat causes neuropathologic changes that are relevant to HAND.…”
Section: Introductionmentioning
confidence: 99%